Transcriptional Repression of p53 by PAX3 Contributes to Gliomagenesis and Differentiation of Glioma Stem Cells - Zhu, Hui; Wang, Hongkui; Huang, Qingfeng; Liu, Qianqian; Guo, Yibing; Lu, Jingjing; Li, Xiaohong; Xue, Chengbin; Han, Qianqian (Frontiers in Molecular Neuroscience, 2018)
Although there are available therapies as surgery, chemotherapy and radiation, glioblastoma (GBM) still has been considered as the most common and overwhelming primary tumor of brain. In GBM, the brain glioma stem cells (BGSCs) were identified and played a crucial role in resistance of GBM to conventional therapies described above. PAX3 was previously identified by our group as a diagnostic/prognostic marker and a therapeutic regulator in the therapy of GBM. Here, we hypothesized PAX3/p53 axis promoted the process of differentiation, regulating to the cancer stem cell properties, such as proliferation and migration. The correlation between PAX3 and p53 in GBM were firstly clarified. Immunofluorescence of p53 was shown activated following BGSCs differentiation. We further identified that PAX3 might specifically bind to the promoter of p53 gene, and transcriptionally repressed p53 expression. ChIP assay further confirmed that PAX3/p53 axis regulated the differentiation process of BGSCs. Then, the function of PAX3 in BGSCs were sequentially investigated in vitro and in vivo. Ectopic PAX3 expression promoted BGSCs growth and migration while PAX3 knockdown suppresses BGSCs growth, migration in vitro and in vivo. Similar to PAX3 overexpression, p53 inhibition also showed increase in growth and migration of differentiated BGSCs. Regarding the functional interaction between PAX3 and p53, PAX3 knockdown-mediated decrease in proliferation was partially rescued by p53 inhibition. Hypoxia significantly promoted the migration potential of BGSCs. In addition, HIF-1α might be a potential upstream regulator of PAX3 in differentiated BGSCs under hypoxia. Our work may provide a supplementary mechanism in regulation of the BGSCs differentiation and their functions, which should provide novel therapeutic targets for GBM in future.